2018
DOI: 10.1016/j.leukres.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Association of red cell distribution width with clinical outcomes in myelodysplastic syndrome

Abstract: Studies showed red cell distribution width (RDW) can improve the detection of morphological changes in red blood cells and the understanding of their contribution to dyserythropoiesis in myelodysplastic syndrome (MDS). The purpose of the study was to evaluate dyserythropoiesis in MDS by RDW analysis and to explore the utility of RDW in clinical practice. We retrospectively analyzed laboratory and clinical data of 101 patients (59 patients was refractory anemia (RA) according to the French-American-British (FAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
1
19
1
1
Order By: Relevance
“…In addition, haemoglobin disorders [35] , myelodysplastic syndromes [36] and red blood cell (RBC) transfusion increased RDW values [37] ; however, we are aware no patients in our series suffered of those disorders or received RBC transfusion before RDW determination.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, haemoglobin disorders [35] , myelodysplastic syndromes [36] and red blood cell (RBC) transfusion increased RDW values [37] ; however, we are aware no patients in our series suffered of those disorders or received RBC transfusion before RDW determination.…”
Section: Discussionmentioning
confidence: 91%
“…RDW, in combination with MPV, may also be interpreted as monitors of bone marrow health. This is demonstrated by increased RDW with age as well as increased rates of hematologic malignancies with higher MPV and RDW which are considered negative independent prognostic factors of survival in myelofibrosis and myelodysplasia [45,51]. In fact Sousa et al, advocated RDW as a novel marker of stress erythropoiesis, which may be induced by systemic inflammatory conditions such as psoriasis [52].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, regression analysis revealed an almost significant correlation coefficient for RET%; thus, it was decided to be included in the final SS with a significant point‐system value. Regarding RDW‐CV%, it has been suggested that increased RDW in MDS might reflect dyserythropoiesis, associated with deregulated hemoglobin synthesis and iron metabolism . Besides that, RDW (in peripheral blood) has been also proposed as an independent predictor of an MDS diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding RDW-CV%, it has been suggested that increased RDW in MDS might reflect dyserythropoiesis, associated with deregulated hemoglobin synthesis and iron metabolism. 22 Besides that, RDW (in peripheral blood) has been also proposed as an independent predictor of an MDS diagnosis. 23 The significant value of RDW-CV% as a discriminant hematological parameter was confirmed in our data.…”
Section: Discussionmentioning
confidence: 99%